CSR EMAT Is an Opportunity for Responsible Decision-Making - Nora Rodek Berkes (Naše gospodarstvo/Our economy, 2022)
Corporate social responsibility is an expected behaviour in Western countries, but the approach still does not have a clear interpretation in Hungary. As a result of the increasing prestige of the CSR approach, socially responsible thinking and action also are expected from the companies operating in Hungary. Company executives carry out CSR activities in many cases – but not consciously. The objective of this research therefore was the development of a guidance and evaluation criteria that can support managers in responsible decision-making and applying the CSR approach to a strategic level. On the other hand, this management tool allows the measurement of CSR excellence in companies; therefore, they become comparable in their CSR performance, which offers opportunities for further research. The study presents the development of CSR EMAT and the results achieved through the measurements.